2005
DOI: 10.1177/000312240507000103
|View full text |Cite
|
Sign up to set email alerts
|

The Discourse of Globalization: Framing and Sensemaking of an Emerging Concept

Abstract: While the literature on framing has importantly expanded our understanding of frame creation and contests from an interpretive point of view, previous studies have largely neglected the structural contexts in which framing activities occur. In this study, we propose extending the framing approach by incorporating insights from the literature on sensemaking to examine how and when opportunities for meaning creation open up and how this affects subsequent discursive processes. Connecting framing and sensemaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
230
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(239 citation statements)
references
References 71 publications
1
230
0
8
Order By: Relevance
“…However, the mechanism for similarity is less clear here, whereas similarity to previous adoptions offers a clear theoretical rationale and empirical mechanisms (i.e., the ability to observe and learn about what parachutes were adopted previously). 5 Because our measure of media attention is considerably correlated with time (r = 0 83), we residualized this measure by regressing it on the linear time variable and then subtracting the predicted values from the measure's actual values, leaving it with only its unique variation, and assigning all confounded variation to the time variable, thus avoiding potential multicollinearity problems (Fiss and Hirsch 2005). Additional robustness checks confirmed that residualization itself has no substantive impact on the results.…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanism for similarity is less clear here, whereas similarity to previous adoptions offers a clear theoretical rationale and empirical mechanisms (i.e., the ability to observe and learn about what parachutes were adopted previously). 5 Because our measure of media attention is considerably correlated with time (r = 0 83), we residualized this measure by regressing it on the linear time variable and then subtracting the predicted values from the measure's actual values, leaving it with only its unique variation, and assigning all confounded variation to the time variable, thus avoiding potential multicollinearity problems (Fiss and Hirsch 2005). Additional robustness checks confirmed that residualization itself has no substantive impact on the results.…”
Section: Discussionmentioning
confidence: 98%
“…Our basic coding unit was a text segment, which we defined as a statement that was meaningful and that expressed a basic yet complete idea (see, for example, Fiss and Hirsch 2005). Aggregation of recurrent idea elements (Gamson and Modigliani 1989) expressed through the text segments yielded themes, or discursive strategies, used by the authors of the texts.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated a two-factor solution in which three of the four items showed very good loadings (.77-.96) and the fourth item (loss of market share) loaded on the predicted factor (economic losses) but also partially on the other (economic gains). We therefore residualized this measure to remove any shared variation with the second factor (e.g., Fiss & Hirsch, 2005). To do so, we regressed this item on the two measures of social and economic gains and then subtracted the predicted values from the actual values, leaving the measure with only its unique variation related to economic losses.…”
Section: Variablesmentioning
confidence: 99%